Expression of mucin 1 possessing a 3′‐sulfated core1 in recurrent and metastatic breast cancer. Issue 7 (7th April 2015) - Ideo, Hiroko; Hinoda, Yuji; Sakai, Kohei; Hoshi, Ikue; Yamamoto, Shigeru; Oka, Masaaki; Maeda, Kazunari; Maeda, Noriko; Hazama, Shoichi; Amano, Junko; Yamashita, Katsuko
<x xml:space="preserve">Abstract</x> Breast cancer is the most frequent cancer threatening the lives of women between the ages of 30 and 64. The cancer antigen 15‐3 assay (CA15‐3) has been widely used for the detection of breast cancer recurrence; however, its sensitivity and specificity are inadequate. We previously found that the breast cancer cell line YMBS secretes mucin 1 possessing 3′‐sulfated core1 (3Score1‐MUC1) into the medium. Therefore, we here evaluated whether 3Score1‐MUC1 is secreted into the blood streams of breast cancer patients, and whether it can serve as an improved breast cancer marker. We developed a lectin‐sandwich immunoassay, called Gal4/MUC1, using a 3′‐sulfated core1‐specific galectin‐4 and a MUC1 monoclonal antibody. Using the Gal4/MUC1 assay method, we found that 3Score1‐MUC1 was profoundly expressed in the blood streams of patients with recurrent and/or metastatic breast cancer. The positive ratio of the Gal4/MUC1 assay was higher than that of the CA15‐3 assay in both primary (n = 240) and relapsed (n = 43) patients, especially in the latter of which the positive ratio of Gal4/MUC1 was 86%. whereas that of CA15‐3 was 47%. Furthermore, serum Gal4/MUC1 levels could more sensitively reflect the recurrence of primary breast cancer patients after surgery. Therefore, the Gal4/MUC1 assay should be an excellent alternative to the CA15‐3 tumor marker for tracking the recurrence and metastasis of breast cancer.